MEASURING OF BANKING SYSTEM RESILIENCE BY USING THE TEXAS RATIO - Mirković, Vladimir; Iliev Matić, Marina; Dudić, Branislav (The European Journal of Applied Economics, 2024)
The issue of banking sector resilience is one of the most exploited after global financial crisis. Competent authorities and central banks worldwide conducted series of actions to strengthen their systems and made it more resilient on extraordinary events. For that purpose, there were conducted stress tests leading to results for improvement of central bank’s supervisory activities and practices. Also, the analysis of banking sector resilience should be complemented with other measures, which are also treated as early warning indicators. Texas ratio is one of the early warning indicators that could indicate the banking system stability through the analysis of non-performing loans as portion of “toxic” assets in banks. High level of non-performing loans represents a huge threat for survival of banking systems, so their monitoring and efficient resolution is imperative. In paper, authors emphasize the significance of Texas ratio usage in the process of banking sector resilience evaluation.
Keywords: resilience, banking sector, non-performing loans, Texas ratio, Republic of Serbia.